Internet-delivered lifestyle physical activity intervention improves body composition in multiple sclerosis: preliminary evidence from a randomized controlled trial - Pilutti, Lara A; Dlugonski, Deirdre; Sandroff, Brian M; Klaren, Rachel E; Motl, Robert W (Archives of physical medicine and rehabilitation, 2014)
To examine the efficacy of a physical activity behavioral intervention for improving outcomes of body composition in persons with multiple sclerosis (MS). Secondary analysis of data from a randomized controlled trial. University research laboratory. Ambulatory persons with MS (N=82). A 6-month, internet-delivered physical activity behavioral intervention designed to increase lifestyle physical activity, primarily walking. The behavioral intervention was based on principles of social cognitive theory. Whole-body bone mineral content (BMC), bone mineral density (BMD), and soft tissue composition, using dual-energy x-ray absorptiometry. There were no significant differences between conditions posttrial on body composition outcomes using the adjusted critical value (P<.008). There was a significant effect of the intervention on whole-body BMC (P=.04, ω(2)<.001) and BMD (P=.01, ω(2)=.003) using the unadjusted critical value (P<.05). The effect of the intervention on percent body fat (P=.09, ω(2)=.001) and whole-body fat mass (P=.05, ω(2)=.003) approached significance using unadjusted criteria. There was not a significant effect on whole-body lean soft tissue (P=.28, ω(2)<.001) or body mass index (P=.86, ω(2)<.001). Our results provide preliminary evidence that an internet-delivered lifestyle physical activity intervention might improve bone health and body composition in MS. Such findings are important considering that physical activity is a modifiable behavior with the potential to confer long-term benefits for the prevention and management of fracture risk and comorbidities among those with MS.